MEMPERKENALKAN SALAH SATU PERMAINAN TRADISIONAL YAITU PERMAINAN NEKERAN PADA ANAK USIA 5-6 TAHUN UNTUK MENINGKATKAN KEMAMPUAN SOSIAL EMOSIONAL ANAK - Arbayah; Fatimah; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2023)
Samarinda,-In this day and age, many children are less exposed to traditional games, most children are busy playing online games on gadgets. A sight that is not regrettable considering that apart from being exciting and fun to play, traditional games also contain a lot of history/philosophy of life. Traditional games have benefits for early childhood in children’s growth compared to gadget games. At this time I am looking at and conducting research on traditional games, one on which is the Nekeran game.The goal is children today still recognize and love traditional game in Indonesia which ore now almost never seen anymore. I also as a researcher use descriptive qualitative methods, in this researchI used data collection technigues with abservastion interviews. The collected data is then analyzed, namely organizing the date, summarizing important points, editing and classifying themes, making a summary.